2009
DOI: 10.1111/j.1654-1103.2009.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of functional diversity reveals the scale and extent of trait convergence and divergence

Abstract: Questions: Trait differentiation among species occurs at different spatial scales within a region. How does the partitioning of functional diversity help to identify different community assembly mechanisms?Location: Northeastern Spain.Methods: Functional diversity can be partitioned into within-community (a) and among-communities (b) components, in analogy to Whittaker's classical a and b species diversity concept. In light of ecological null models, we test and discuss two algorithms as a framework to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
228
2
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(258 citation statements)
references
References 57 publications
(173 reference statements)
17
228
2
6
Order By: Relevance
“…2). Similar results have been obtained by de Bello et al (2009) for plant communities in pastures along an altitude gradient in Spain. It is worth noting that the β Simpson diversity index and β species richness are different measures of species turnover among communities (Pavoine et al, 2004).…”
Section: Discussionsupporting
confidence: 76%
“…2). Similar results have been obtained by de Bello et al (2009) for plant communities in pastures along an altitude gradient in Spain. It is worth noting that the β Simpson diversity index and β species richness are different measures of species turnover among communities (Pavoine et al, 2004).…”
Section: Discussionsupporting
confidence: 76%
“…[5,16,17]. For instance, de Bello et al [16] found that within-site variation of SLA accounted for approximately 90% of the total observed variation across regional climatic gradients.…”
Section: Introductionmentioning
confidence: 99%
“…[5,16,17]. For instance, de Bello et al [16] found that within-site variation of SLA accounted for approximately 90% of the total observed variation across regional climatic gradients. At a larger scale, more than one-third of the total global variation in SLA occurs within areas of similar abiotic conditions, as opposed to among sites that vary with respect to climate variables [5].…”
Section: Introductionmentioning
confidence: 99%
“…d ij is the trait dissimilarity between each pair of taxa i and j measured as Euclidean distance. Accordingly, FD RAO is the sum of the trait dissimilarities among all possible pairings of taxa, weighted by the relative abundance of the taxa (de Bello et al 2009). FD RAO was calculated separately for each of the 11 biological traits and summed up for the entire assemblage of a site (Darr et al 2014;van der Molen et al 2013).…”
Section: Methodsmentioning
confidence: 99%